Impactful women directors and earnings management - Mujeeb Saif Mohsen Al-Absy (Cogent Business & Management, 2022)
A board with high equality is expected to play a significant role in corporate governance. This study aims to examine the influence of impactful women directors on constraining the level of earnings management (EM). Impactful women director is a new concept examined by the study, where women directors on board must be serving in the audit committee (AC). Having women on the board who also serves on the AC will strengthen the role and power of women directors in mitigating EM. The study covers companies with the lowest positive return on assets. Based on the regression, the results of the study seem to be in line with the theories of agency and resource dependence. There is a significant negative relationship between the impactful women directors and the level of EM, accrual, and real earnings management. Having at least one female director who also serves on the AC enhances the effectiveness of the board and then, significantly constrains EM. Likewise, having at least two female directors and at least one of them serving on the AC could improve their participation in decision-making and effectively monitor the managers' behavior toward engaging in EM. The study is very useful for policymakers, stakeholders, researchers, and society. Firms should appoint more women directors on board and at the same time appoint at least one of them at the AC to strengthen their role in monitoring and supervising the management.
Keywords: 650; audit committee; Corporate governance; board of directors; earnings management; women directors